2008
DOI: 10.1593/neo.08134
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic Drugs Induce PPAR-γ Expression and Show Sequence-Specific Synergy with PPAR-γ Ligands in Inhibition of Non–Small Cell Lung Cancer

Abstract: Preclinical studies have shown that peroxisome proliferator-activated receptor gamma (PPAR-gamma) ligands can exert antitumor effects against non-small cell lung cancer (NSCLC) and a variety of other cancers. In this study, we investigate the potential use of a PPAR-gamma ligand, troglitazone (Tro), in combination with either of two chemotherapeutic agents, cisplatin (Cis) or paclitaxel (Pac), for the treatment of NSCLC. In vitro, treatment of NSCLC cell lines with Tro potentiated Cis- or Pac-induced growth in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…Earlier trials, testing PPAR-γ ligands as mono-therapy, in a very small number of advanced stage prostate and breast cancer patients failed to show a therapeutic benefit (39-41). Interestingly, recent studies (42, 43), including ours (21), assessing the use of PPAR-γ ligands in combination with standard chemotherapeutic agents demonstrated synergistic effect. Whereas, colorectal cancer cells resistant to oxaliplatin or ovarian cancer cells resistant to paclitaxel both exhibit EMT phenotype (44, 45).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Earlier trials, testing PPAR-γ ligands as mono-therapy, in a very small number of advanced stage prostate and breast cancer patients failed to show a therapeutic benefit (39-41). Interestingly, recent studies (42, 43), including ours (21), assessing the use of PPAR-γ ligands in combination with standard chemotherapeutic agents demonstrated synergistic effect. Whereas, colorectal cancer cells resistant to oxaliplatin or ovarian cancer cells resistant to paclitaxel both exhibit EMT phenotype (44, 45).…”
Section: Discussionmentioning
confidence: 75%
“…We have also shown that treatment of mice with PPAR-γ agonists inhibits tumor progression of A549 xenografts in SCID-beige mice (20). Recently we showed chemotherapeutic drugs induce PPAR-γ expression and show sequence specific synergy with PPAR-γ ligands in inhibition of NSCLC (21). In the current study we demonstrate a novel mechanism of PPAR-γ dependent inhibition of EMT in tumor cells, by antagonizing Smad3 function.…”
Section: Introductionmentioning
confidence: 99%
“…PPARγ has roles in acute and chronic inflammatory responses in the lung (5759), pulmonary fibrosis (57, 60), lung cancer (61) and pulmonary vascular disease (62); however, specific roles of PPARγ in lung development have yet to be determined. The discovery that PPARγ regulates the expression of chromatin modifying enzymes (16) suggests that PPARγ’s role in lung development may be via the regulation of epigenetic events.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro treatment of human non‐small‐cell lung cancer cells with PPARγ activators induced differentiation and apoptosis (Chang and Szabo, 2000; Inoue et al ., 2001; Satoh et al ., 2002), as well as potentiated the inhibitory effects of cisplatin and paclitaxel (Reddy et al ., 2008). In vivo experiments using a xenograft model showed similar results (Keshamouni et al ., 2005).…”
Section: Ppars and Lung Cancermentioning
confidence: 99%